Diverse functions of pericytes in cerebral blood flow regulation and ischemia - Fernández-Klett, Francisco (J Cereb Blood Flow Metab, 2015)
Pericytes are mural cells with contractile properties. Here, we provide evidence that microvascular pericytes modulate cerebral blood flow in response to neuronal activity (‘functional hyperemia'). Besides their role in neurovascular coupling, pericytes are responsive to brain damage. Cerebral ischemia is associated with constrictions and death of capillary pericytes, followed by fibrotic reorganization of the ischemic tissue. The data suggest that precapillary arterioles and capillaries are major sites of hemodynamic regulation in the brain.